A survey on lower secondary school students’ motivation to take extra courses in English: M.A. Thesis Linguistics: 82202 - Nguyễn, Thúy Lan Anh (2019)
English is more and more essential in the modern world because this language supports people a lot in their academic career or jobs. For students, English is vital if they want to get scholarships for studying abroad or it is the important factor which provides learners access to gifted schools. Although teaching and learning English are improved a lot in Vietnamese schools, many students find extra courses to help them promoting their English proficiency.